2019
DOI: 10.1113/jp278237
|View full text |Cite
|
Sign up to set email alerts
|

Chronic statin therapy is associated with enhanced cutaneous vascular responsiveness to sympathetic outflow during passive heat stress

Abstract: Key points Impairments in both central sympathetic and peripheral microvascular function contribute to blunted reflex cutaneous vasodilatation during heat stress in healthy older adults. Hypercholesterolaemia is associated with decrements in neurovascular function; however, little is known about the impact of hypercholesterolaemia on the integrated responses to heat stress. Further, whether chronic statin therapy alters skin sympathetic outflow or its relation to cutaneous vascular conductance during heat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 65 publications
(229 reference statements)
3
15
0
Order By: Relevance
“…Once activated, the gain (or sensitivity of the response) is a proportional value that reflects the relation between the magnitude of the input signal (in this case, mean body temperature, � T b ) and the magnitude of the output signal (SSNA and CVC/sweat rate). Retrospectively applying this control theory approach, we tested the hypothesis that the � T b threshold for activation of SSNA would be increased, but, consistent with our previous studies [8,12,13], the sensitivity of the response (gain) would be reduced, in healthy older compared to young adults.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Once activated, the gain (or sensitivity of the response) is a proportional value that reflects the relation between the magnitude of the input signal (in this case, mean body temperature, � T b ) and the magnitude of the output signal (SSNA and CVC/sweat rate). Retrospectively applying this control theory approach, we tested the hypothesis that the � T b threshold for activation of SSNA would be increased, but, consistent with our previous studies [8,12,13], the sensitivity of the response (gain) would be reduced, in healthy older compared to young adults.…”
Section: Introductionmentioning
confidence: 83%
“…The resultant afferent neural signals are relayed to brainstem regions, primarily the preoptic anterior hypothalamus; central integration of this thermosensory input results in an increase in efferent skin sympathetic nervous system activity (SSNA) to activate eccrine sweating and cutaneous vasodilation -the primary thermoeffector mechanisms for heat dissipation [10,11]. A series of studies from our laboratory [8,[11][12][13] has demonstrated significant functional deficits at multiple points along the efferent thermoregulatory reflex axis in healthy older adults. First, the increase in SSNA during whole-body heating is markedly blunted [8,12], a central neural limitation that appears to be specific to thermoregulatory stimuli [8,14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations